Belowground phytomass and production in the beech ecosystem Calamintho grandiflorae-Fagetum in Mavrovo National Park. III. Fine root phytomass of trees and shrubs - Hristovski, Slavčo; Melovski, Ljupčo; Šušlevska, Marjana; Grupče, Ljupčo (Macedonian Journal of Ecology and Environment, 2008)
The fine root biomass (d < 2 mm) in the beech ecosystem Calamintho grandiflorae-Fagetum in Mavrovo National Park is presented. Fine roots were separated into live (10.16 t·ha-1) and dead (6.33 t·ha-1) roots. Live roots were divided into four fractions (<0.2; 0.2-0.5; 0.5-1.0 and 1.0-2.0 mm) which from the smallest roots (d < 0.2 mm) were dominant. The mass of the fractions decreased with the increase of the fine root diameter. Dead roots were divided into two fractions (<1.0 and 1.0-2.0 mm). Fine root mass was investigation up to 150 cm depth. The largest biomass was recorded in the first 10 cm of the soil (35.8%). The mass of fine roots decreased with the depth according to a linear model. Comparison of the results with literature data for other forest ecosystems revealed that the fine root biomass in the investigated beech ecosystem in Mavrovo National Park is similar or higher.